Research robustness optimal control systems thermal object - Lutska, N. (Енергетика і автоматика, 2015)
The mathematical model of control object that describes the temperature regime tilted diffusion sugar factory settings and flashy sources of uncertainty parameters. Past studies of the optimal control system regulator, which is synthesized in minimizatsiyi N∞ standards-transfer function of the system showed the feasibility of its use by the action of various kinds of perturbations and when changing the subject.